ANALISIS KESULITAN BELAJAR MEMBACA DAN MENULIS PADA SISWA KELAS 4 DI SDN CIBODAS 4 KOTA TANGERANG - Encep Andriana; Siti Rokmanah; Nabila Fatmala; Rizki Wulan (STKIP Subang, 2023)
This research was motivated by the researcher's observations regarding difficulties in learning to read and write among students in grade 4 which occurred at SDN Cibodas 4, Tangerang City. This research aims to obtain information or a clear picture of how difficult learning to read and write is carried out at SDN Cibodas 4 Tangerang City with the learning outcomes achieved by grade 4 students. The research population is all grade 4 students consisting of one class with 40 students. This type of research is qualitative research using a descriptive approach research method, where data collection uses interview, observation and documentation techniques. Based on the results of this research, several difficulties experienced by students were found, including: (1) Difficulty recognizing letters when reading, (2) Difficulty with spelling and unclear reading pronunciation among students, (3) Many errors in reading among students, (4) Difficulty distinguishing several letters when writing, (5) Lack of letters when writing words, (6) The time required to write is too long, and several solutions that can be done to overcome difficulties in learning to read and write in students that have been found in 4th grade at SDN Cibodas 4, Tangerang City. Keywords: Difficulty Learning, Reading, Writing